Corporate Governance and Performance: An Empirical Investigation of Sugar Producing Companies in Kenya - V.N., Machuki,; J.O., Rasowo, (European Scientific Journal, ESJ, 2018)
Corporate governance is concerned with the running of an organization in a way that guarantees that its owners or stockholders receive a fair return on their investments while the expectations of other stakeholders are also met. The study sought to examine the relationship between corporate governance practices and performance of sugar producing companies in Kenya. The study intended to establish the corporate governance practices adopted by the companies and the influence of these practices on their performance. Through a cross-sectional survey of 11 companies, data were gathered using a structured questionnaire and analyzed using both descriptive and inferential statistics. The results indicate that all the studied companies practice some form of corporate governance although the degree of adoption differ across them. The study also revealed that board decisions are not influenced by founder members and that it was not common for board members to engage in financial transactions with the companies. The results of regression analysis show that overall, there is a positive and statistically significant influence of corporate governance practices on performance of the sugar producing companies. The study draws a conclusion that a combination of good corporate governance practices is responsible for a large percentage of good performance achieved by the sugar companies. Individual corporate governance practices acting on their own do not always lead to improved performance. The study offers support for theories that anchor performance implications of good corporate governance as well as findings of previous similar studies. Based on the findings of the study, recommendation for policy and practice are made as well as suggestions for further research.